The extended clinical and genetic spectrum of CTNNB1-related neurodevelopmental disorder - Lee, Seungbok; Jang, Se Song; Park, Soojin; Yoon, Jihoon G.; Kim, Soo Yeon; Lim, Byung Chan; Chae, Jong Hee (Frontiers in Pediatrics, 2022)
Purpose: Loss-of-function mutations of CTNNB1 have been established as the cause of neurodevelopmental disorder with spastic diplegia and visual defects. Although most patients share key phenotypes such as global developmental delay and intellectual disability, patients with CTNNB1-related neurodevelopmental disorder show a broad spectrum of clinical features. Methods: We enrolled 13 Korean patients with CTNNB1-related neurodevelopmental disorder who visited Seoul National University Children’s Hospital (5 female and 8 male patients with ages ranging from 4 to 22 years). They were all genetically confirmed as having pathogenic loss-of-function variants in CTNNB1 using trio or singleton whole exome sequencing. Variants called from singleton analyses were confirmed to be de novo through parental Sanger sequencing. Results: We identified 11 de novo truncating variants in CTNNB1 in 13 patients, and two pathogenic variants, c.1867C>T (p.Gln623Ter) and c.1420C>T (p.Arg474Ter), found in two unrelated patients, respectively. Five of them were novel pathogenic variants not listed in the ClinVar database. While all patients showed varying degrees of intellectual disability, impaired motor performance, and ophthalmologic problems, none of them had structural brain abnormalities or seizure. In addition, there were three female patients who showed autistic features, such as hand stereotypy, bruxism, and abnormal breathing. A literature review revealed a female predominance of autistic features in CTNNB1-related neurodevelopmental disorder. Conclusion: This is one of the largest single-centre cohorts of CTNNB1-related neurodevelopmental disorder. This study investigated variable clinical features of patients and has expanded the clinical and genetic spectrum of the disease.